2010
DOI: 10.1111/j.1469-8749.2009.03567.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cognitive and adaptive behaviour among individuals with congenital insensitivity to pain and anhidrosis

Abstract: Aim  Individuals with congenital insensitivity to pain with anhidrosis (CIPA) are reported to have mental retardation* but to our knowledge no detailed study on the subject has ever been published. The present study assessed and documented cognitive and adaptive behaviour among Arab Bedouin children with CIPA. Methods  Twenty‐three Arab Bedouin children (12 females, 11 males) with CIPA aged between 3 and 17 years (mean 9y 7mo, SD 4y 2mo) were assessed. They were compared with 19 healthy siblings of the affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The absence of mental retardation is also a feature that distinguishes Norrbottnian HSAN V from both Arab HSAN V and HSAN IV symptoms. Indeed, Arab HSAN V patients are reported to show a delay in mental development (Carvalho et al, 2010), and HSAN IV children suffer severe attention deficit hyperactivity disorder (ADHD; Levy Erez et al, 2010). In the Norrbottnian family only one child showed mild symptoms of ADHD .…”
Section: Mechanisms Of Disease: Impact On Prongf and Ngf Functionmentioning
confidence: 99%
“…The absence of mental retardation is also a feature that distinguishes Norrbottnian HSAN V from both Arab HSAN V and HSAN IV symptoms. Indeed, Arab HSAN V patients are reported to show a delay in mental development (Carvalho et al, 2010), and HSAN IV children suffer severe attention deficit hyperactivity disorder (ADHD; Levy Erez et al, 2010). In the Norrbottnian family only one child showed mild symptoms of ADHD .…”
Section: Mechanisms Of Disease: Impact On Prongf and Ngf Functionmentioning
confidence: 99%
“…It is likely that patients with CIPA lack these cholinergic neurons. Assessments of cognitive and adaptive behavior have suggested that many children with CIPA exhibit mental retardation (or learning disabilities) and symptoms of severe attention deficit hyperactivity disorder (Levy Erez et al ., ). Thus, at least some symptoms related to cognitive and adaptive behaviors in CIPA may be caused by the role of cholinergic neurons in attention and memory mechanisms.…”
Section: Functions Of Neurons In Brain Regions That Express Trka Mrnamentioning
confidence: 97%
“…Behaviors of children with CIPA are often characterised as labile, hyperactive and erratic. Assessments of cognitive and adaptive behavior have suggested that many children with CIPA exhibit mental retardation (or learning disabilities) and symptoms of severe attention-deficit-hyperactivity disorder (Levy Erez et al, 2010).…”
Section: Congenital Insensitivity To Pain With Anhidrosismentioning
confidence: 99%
See 1 more Smart Citation
“…They found that these children had lower scores in the intelligence test and the adaptive behavior scale compared with their healthy siblings. IQ was significantly higher among children aged up to 7 years than among the older children . In examinations of Japanese children with HSAN‐IV, Shirakawa and Nihei found that development is variable in preschool children, and reduced interest in objects, a lack of communication, speech delay, autistic traits, and ADHD symptoms, are often observed.…”
Section: Complications and Their Managementmentioning
confidence: 98%